Pengaruh Kebijakan Ketenagakerjaan Daerah terhadap Produktivitas dan Penyerapan Tenaga Kerja di Provinsi Banten - Muhit, Abdul; Dian Evariana; Siti Sofiyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the effect of regional employment policies on labor productivity and employment absorption in Banten Province. A quantitative approach was employed using an explanatory research method through surveys of active workers in the industrial, trade, and service sectors. Primary data were collected using questionnaires, while secondary data were obtained from the Central Statistics Agency (BPS) and official local government documents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS). The findings reveal that employment policies have a positive and significant effect on both labor productivity and employment absorption. Labor productivity also positively influences employment absorption. Job training programs are identified as the most effective policy indicator, while job placement services require improvement, particularly through the utilization of digital technology. The study recommends strengthening cross-sector coordination, optimizing digital job market platforms, and integrating employment policies with regional investment strategies to create a productive, inclusive, and competitive labor market.